Repetitive head injury in adolescent mice: A role for vascular inflammation. Issue 11 (November 2019) - Wu, Limin; Chung, Joon Y; Saith, Shivani; Tozzi, Lorenzo; Buckley, Erin M; Sanders, Bharat; Franceschini, Maria A; Lule, Sevda; Izzy, Saef; Lok, Josephine; Edmiston, William J; McAllister, Lauren M; et al.
Repetitive mild traumatic brain injury during adolescence can induce neurological dysfunction through undefined mechanisms. Interleukin-1 (IL-1) contributes to experimental adult diffuse and contusion TBI models, and IL-1 antagonists have entered clinical trials for severe TBI in adults; however, no such data exist for adolescent TBI. We developed an adolescent mouse repetitive closed head injury (rCHI) model to test the role of IL-1 family members in post-injury neurological outcome. Compared to one CHI, three daily injuries (3HD) produced acute and chronic learning deficits and emergence of hyperactivity, without detectable gliosis, neurodegeneration, brain atrophy, and white matter loss at one year. Mature IL-1β and IL-18 were induced in brain endothelium in 3HD but not 1HD, three hit weekly, or sham animals. IL-1β processing was induced cell-autonomously in three-dimensional human endothelial cell cultures subjected to in vitro concussive trauma. Mice deficient in IL-1 receptor-1 or caspase-1 had improved post-injury Morris water maze performance. Repetitive mild CHI in adolescent mice may induce behavioral deficits in the absence of significant histopathology. The endothelium is a potential source of IL-1β and IL-18 in rCHI, and IL-1 family members may be therapeutic targets to reduce or prevent neurological dysfunction after repetitive mild TBI in adolescents.